Overview of Systematic Reviews on Factors Related to the Structure and Functioning of Residential Long-Term Care Facilities for Older Adults - Aurélio Matos Andrade; Karine Rodrigues Afonseca; Tatiana de Almeida Jube; Suelen Meira Góes; Maíra Catharina Ramos; Flavia Tavares da Silva Elias (Geriatrics, 2025)
Objective: To identify factors influencing the structure and functioning of long-term residential care facilities for older adults worldwide, in order to uncover practices and support evidence-based improvements in care delivery. Method: An overview of systematic reviews was performed according to the PRISMA protocol and registered on the PROSPERO platform (no. CRD42023486204). Research was carried out on 21 September 2023, using the following databases: PubMed (via MedLine), EMBASE, Web of Science, Scopus, Virtual Health Library (VHL), and Epistemonikos. Results: The search yielded 12,040 articles, including 61 systematic reviews. Analyzing the primary outcomes, personnel structure, and risk management were the most-studied outcomes of the systematic reviews, followed by pharmaceuticals, food services, mobility/accessibility, and technological and physical structures. In terms of primary outcomes of the systematic reviews, the personnel structure was the most highlighted (in 39.34%), followed by risk management (in 32.79%), while the least highlighted was physical structure (in 9.84%). Conclusions: Personnel are critical to the safe and effective functioning of Long-Term Care Facility (LTCF) operations. Future research is needed to identify associations between models of care and structural concerns, including physical environment, as they relate to quality of care in LTCFs, particularly in low and middle-income countries (LMIC).